Neoproterozoic Bimodal Intrusive Complex in the Southwestern Tarim Block, Northwest China: Age, Geochemistry, and Implications for the Rifting of Rodinia - Zhang, C.; Li, Zheng-Xiang; Li, X.; Ye, H.; Wang, A.; Guo, K. (V H Winston & Son Inc, 2006)
We report here the first SHRIMP U-Pb zircon ages and bulk-rock geochemistry for a Neoproterozoicbimodal intrusive complex in the Tarim block and discuss the tectonic implications. The Kudiigneous complex (KIC) crystallized at 783 10 Ma. Granite and gabbro comingled, indicating thatthe intrusions were coeval. The granite displays: high total alkalis (Na2O + K2O = 8?11 wt%); highabundances of Zr, Nb, Y, and total REE; and strong LREE enrichment [(La/Yb)N = 9?59] with asignificant negative Eu anomaly (dEu = 0.17?0.44), characteristic of A-type granites. Furthermore,samples of the granite have homogeneous positive eNd(T) values of 1.4 to 2.1 and MesoproterozoicNd modal ages (~1.3 Ga). We thus interpret the granite as probably generated by partial melting ofthe regional Mesoproterozoic arc and/or back-arc crust. The KIC gabbro is geochemically similar tointraplate alkaline basalts, with trace elements and isotope compositions indicating an OIB-typemagma source, variably contaminated by continental crust. Field observations, petrology, andgeochemistry indicate that the KIC was a bimodal alkaline complex formed by mixing of these twomagma types of different origins in a continental rift, possibly related to a mantle superplumebeneath the Rodinian supercontinent.